2019
DOI: 10.4172/0974-8369.1000023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malathion on liver ache activity of mice

Abstract: An experiment was conducted to study the effect of malathion toxicity on acetylcholinesterase activity in mice liver. Mature mice were exposed to different doses of malathion for different time period. On dissections, enzymatic estimations were done for each exposure period. It was found that, malathion inhibited the acetylcholinesterase activity in mice liver .The maximum period of exposure was upto 30 days. The degree of inhibition increased upto 4 days of exposure period but declined later on. There was max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In an experimental study conducted to investigate the effect of malathion toxicity on acetylcholinesterase activity in mice, mature mice were exposed to malathion at different doses at different times. It was found that malathion inhibited acetylcholinesterase activity in liver (Wankhade et al, 2009). It was observed that the acetylcholineesterase activity in the MAL group was statistically significantly lower when compared to all other groups (p <0.05) as demonstrated in Table 5.…”
Section: Groupmentioning
confidence: 77%
“…In an experimental study conducted to investigate the effect of malathion toxicity on acetylcholinesterase activity in mice, mature mice were exposed to malathion at different doses at different times. It was found that malathion inhibited acetylcholinesterase activity in liver (Wankhade et al, 2009). It was observed that the acetylcholineesterase activity in the MAL group was statistically significantly lower when compared to all other groups (p <0.05) as demonstrated in Table 5.…”
Section: Groupmentioning
confidence: 77%
“…Aer that, the Zn and Co supported catalyst was tested for its activity (Table 3 entries 19-24). Then solvents like MeOH, acetonitrile, toluene, DCM, DMF, DMSO and solventfree conditions were used for the reaction (Table 3 entries [25][26][27][28][29][30][31][32][33][34][35]. Aer checking the catalytic activity of various catalysts, the Cu/zeolite-Y catalyst was found to be efficient for this reaction.…”
Section: Optimization Of Reaction Parametersmentioning
confidence: 99%
“…Quinoline derivatives undergo hierarchical self-assembly into a variety of nanostructures and mesostructures with enhanced electronic and photonic functions as well as medicinal applications. 26 Indenoquinoline derivatives showed a wide range of biological activities such as 5-HT-receptor binding activity, 27 anti-inammatory activity and they also act as anti-tumor agents, 28 inhibitors for steroid reductase, 29 acetylcholinesterase inhibitors, 30 show antimycobacterial 31 and antiproliferative activities 32 and act as antimalarials. 33 Also, these compounds serve as the building blocks of many natural-chromophore DNA intercalators such as TAS 103, 34 DACA, 35,36 and NSC 314622, 37 which are currently being used as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%